2004
DOI: 10.1002/anie.200400654
|View full text |Cite
|
Sign up to set email alerts
|

When and How Do Diaminocarbenes Dimerize?

Abstract: No example of a simple uncatalyzed dimerization of a diaminocarbene has been clearly established, so it is timely to ask what factors control the thermodynamics of this reaction, and what mechanisms are responsible for the observed dimerizations? In agreement with qualitative experimental observations, the dimerizations of simple five- and six-membered-ring diaminocarbenes are calculated to be 100 kJ mol(-1) less favorable than those of acyclic counterparts. This large difference is semiquantitatively accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
182
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(193 citation statements)
references
References 86 publications
9
182
0
Order By: Relevance
“…Although the endocyclic B-N bonds are slightly shorter, the C-N bond lengths are quite similar to those of Da, because the phenyl ring at boron is coplanar with the four-membered ring and acts as a donor. However, this alteration enhanced the electrophilicity of the endocyclic carbon and boron atoms of Db as shown by the 13 C (194.1 ppm) and 11 B NMR signals (45.7 ppm), which are shifted downfield by 11.4 and 17.7 ppm, respectively, relative to those of Da. In fact, the heterocyclic salt Db appears to be very fragile; it quickly decomposes even in weakly coordinating solvents such as Et 2 O, THF, CH 2 Cl 2 , and CHCl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the endocyclic B-N bonds are slightly shorter, the C-N bond lengths are quite similar to those of Da, because the phenyl ring at boron is coplanar with the four-membered ring and acts as a donor. However, this alteration enhanced the electrophilicity of the endocyclic carbon and boron atoms of Db as shown by the 13 C (194.1 ppm) and 11 B NMR signals (45.7 ppm), which are shifted downfield by 11.4 and 17.7 ppm, respectively, relative to those of Da. In fact, the heterocyclic salt Db appears to be very fragile; it quickly decomposes even in weakly coordinating solvents such as Et 2 O, THF, CH 2 Cl 2 , and CHCl 3 .…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that six--electron NHCs B (6), isoelectronic with borazenes (7), are highly thermally stable. Even more strikingly, the two--electron cyclopropenylidene C is stable enough to be isolated at room temperature (8), despite the absence of -donor heteroatoms directly bonded to the carbene center, a necessary criterion for previously isolated carbenes (9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Besides the deprotonation of azolium salts, some additional, less commonly applied methods for the formation of free NHCs exist (Scheme 2), and they might have attractive features, such as a simpler purification or a slow in situ formation of the NHC: [17] -Desulfurization of thioureas with molten potassium in boiling THF (Scheme 2 b). An attractive feature of this method is the insolubility of the by-product (potassium sulfide) in THF.…”
Section: Generation Of Free Nhcsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Structural classes embodied within the NHC family include the thiazol-2-ylidenes 1, imidazol-2-ylidenes 2 and imidazolin-2-ylidenes 3, trihydropyrimidin-2-ylidenes 4 and triazol-3-ylidenes 5. From the early seminal work of Breslow, 13 thiazol-2-ylidenes such as 1 have long been implicated as the catalytically active species in the benzoin condensation, however, until recently, applications beyond this C-C bond-forming reaction were relatively limited.…”
mentioning
confidence: 99%